From digital holographic microscopy to optical coherence tomography – separate past and a common goal - Kuś, Arkadiusz; Krauze, Wojciech; Kujawińska, Małgorzata (Photonics Letters of Poland, 2021)
In this paper we briefly present the history and outlook on the development of two seemingly distant techniques which may be brought close together with a unified theoretical model described as common k-space theory. This theory also known as the Fourier diffraction theorem is much less common in optical coherence tomography than its traditional mathematical model, but it has been extensively studied in digital holography and, more importantly, optical diffraction tomography. As demonstrated with several examples, this link is one of the important factors for future development of both techniques. Full Text: PDF References N. Leith, J. Upatnieks, "Reconstructed Wavefronts and Communication Theory", J. Opt. Soc. Am. 52(10), 1123 (1962). CrossRef Y. Park, C. Depeursinge, G. Popescu, "Quantitative phase imaging in biomedicine", Nat. Photonics 12, 578 (2018). CrossRef D. Huang et al., "Optical Coherence Tomography", Science 254(5035), 1178 (1991). CrossRef D. P. Popescu, C. Flueraru, S. Chang, J. Disano, S. Sherif, M.G. Sowa, "Optical coherence tomography: fundamental principles, instrumental designs and biomedical applications", Biophys. Rev. 3(3), 155 (2011). CrossRef M. Wojtkowski, V. Srinivasan, J.G. Fujimoto, T. Ko, J.S. Schuman, A. Kowalczyk, J.S. Duker, "Three-dimensional Retinal Imaging with High-Speed Ultrahigh-Resolution Optical Coherence Tomography", Ophthalmology 112(10), 1734 (2005). CrossRef K.C. Zhou, R. Qian, A.-H. Dhalla, S. Farsiu, J.A. Izatt, "Unified k-space theory of optical coherence tomography", Adv. Opt. Photon. 13(2), 462 (2021). CrossRef A.F. Fercher, C.K. Hitzenberger, G. Kamp, S.Y. El-Zaiat, "Measurement of intraocular distances by backscattering spectral interferometry", Opt. Comm. 117(1-2), 43 (1995). CrossRef E. Wolf, "Determination of the Amplitude and the Phase of Scattered Fields by Holography", J. Opt. Soc. Am. 60(1), 18 (1970). CrossRef E. Wolf, "Three-dimensional structure determination of semi-transparent objects from holographic data", Opt. Comm. 1(4), 153 (1969). CrossRef V. Balasubramani et al., "Roadmap on Digital Holography-Based Quantitative Phase Imaging", J. Imaging 7(12), 252 (2021). CrossRef A. Kuś, W. Krauze, P.L. Makowski, M. Kujawińska, "Holographic tomography: hardware and software solutions for 3D quantitative biomedical imaging (Invited paper)", ETRI J. 41(1), 61 (2019). CrossRef A. Kuś, M. Dudek, M. Kujawińska, B. Kemper, A. Vollmer, "Tomographic phase microscopy of living three-dimensional cell cultures", J. Biomed. Opt. 19(4), 46009 (2014). CrossRef O. Haeberlé, K. Belkebir, H. Giovaninni, A. Sentenac, "Tomographic diffractive microscopy: basics, techniques and perspectives", J. Mod. Opt. 57(9), 686 (2010). CrossRef B. Simon et al., "Tomographic diffractive microscopy with isotropic resolution", Optica 4(4), 460 (2017). CrossRef B.A. Roberts, A.C. Kak, "Reflection Mode Diffraction Tomography", Ultrason. Imag. 7, 300 (1985). CrossRef M. Sarmis et al., "High resolution reflection tomographic diffractive microscopy", J. Mod. Opt. 57(9), 740 (2010). CrossRef L. Foucault et al., "Versatile transmission/reflection tomographic diffractive microscopy approach", J. Opt. Soc. Am. A 36(11), C18 (2019). CrossRef W. Krauze, P. Ossowski, M. Nowakowski, M. Szkulmowski, M. Kujawińska, "Enhanced QPI functionality by combining OCT and ODT methods", Proc. SPIE 11653, 116530B (2021). CrossRef E. Mudry, P.C. Chaumet, K. Belkebir, G. Maire, A. Sentenac, "Mirror-assisted tomographic diffractive microscopy with isotropic resolution", Opt. Lett. 35(11), 1857 (2010). CrossRef P. Hosseini, Y. Sung, Y. Choi, N. Lue, Z. Yaqoob, P. So, "Scanning color optical tomography (SCOT)", Opt. Expr. 23(15), 19752 (2015). CrossRef J. Jung, K. Kim, J. Yoon, Y. Park, "Hyperspectral optical diffraction tomography", Opt. Expr. 24(3), 1881 (2016). CrossRef T. Zhang et al., Biomed. "Multi-wavelength multi-angle reflection tomography", Opt. Expr. 26(20), 26093 (2018). CrossRef R.A. Leitgeb, "En face optical coherence tomography: a technology review [Invited]", Biomed. Opt. Expr. 10(5), 2177 (2019). CrossRef J.F. de Boer, R. Leitgeb, M. Wojtkowski, "Twenty-five years of optical coherence tomography: the paradigm shift in sensitivity and speed provided by Fourier domain OCT [Invited]", Biomed. Opt. Expr. 8(7), 3248 (2017). CrossRef T. Anna, V. Srivastava, C. Shakher, "Transmission Mode Full-Field Swept-Source Optical Coherence Tomography for Simultaneous Amplitude and Quantitative Phase Imaging of Transparent Objects", IEEE Photon. Technol. Lett. 23(11), 899 (2011). CrossRef M.T. Rinehart, V. Jaedicke, A. Wax, "Quantitative phase microscopy with off-axis optical coherence tomography", Opt. Lett. 39(7), 1996 (2014). CrossRef C. Photiou, C. Pitris, "Dual-angle optical coherence tomography for index of refraction estimation using rigid registration and cross-correlation", J. Biomed. Opt. 24(10), 1 (2019). CrossRef Y. Zhou, K.K.H. Chan, T. Lai, S. Tang, "Characterizing refractive index and thickness of biological tissues using combined multiphoton microscopy and optical coherence tomography", Biomed. Opt. Expr. 4(1), 38 (2013). CrossRef K.C. Zhou, R. Qian, S. Degan, S. Farsiu, J.A. Izatt, "Optical coherence refraction tomography", Nat. Photon. 13, 794 (2019). CrossRef